An Overview of Queens Estrous Cycle - Zabuli , Jahid (Journal of Natural Sciences – Kabul University, 2023)
In the world, with the increasing trade of cats; In order to keep at home, as a companion and experimental animal in research, in our country to control the population of house mice, it has become more important in human life. In the view point of cat, population control, it is also important to be considered. Keeping in mind the mentioned cases of using cats as valuable research models and the occurrence of cases of low fertility and infertility in cats of modified breed, paying attention to the state of reproduction and their management has become more important. This article aims to study the estrous cycle of domestic cats (queen), taking into account the general characteristics of reproduction, breeding season, clinical considerations and hormonal changes. Review of the above topic opens the way of intervention and management of reproduction in this animal species.